195PHGCSG1601: A retrospective cohort study of the efficacy and safety of nab-paclitaxel plus gemcitabine (nab-P+GEM) for unresectable locally advanced pancreatic cancer (LAPC). (24th November 2019) - Tanimoto, A; Yagisawa, M; Nakano, S; Kawamoto, Y; Yuki, S; Ishiguro, A; Takahata, T; Sato, A; Iwanaga, I; Ehira, N; Uebayashi, M; Muto, O; et al.
Abstract: Background: The regimens of nab-P+GEM have become available for advanced pancreatic cancer, especially metastatic disease. However, there are not enough data of nab-P+GEM for LAPC. Methods: This is a retrospective multiple institutes cohort study using medical records of LAPC patients who received nab-P+GEM between January 2015 and September 2017. We have surveyed their characteristics and treatment outcomes. Results: The number of relevant patients was 48 at 11 institutes. Median age was 68 years old, male/female : 22/26, ECOG PS 0/1/2 : 33/13/2, primary site; head/body/tail : 28/18/2. Relative dose intensity was nab-P; 0.588 (0.065-1.012) and GEM; 0.656 (0.368-1.012). Response rate was 27.0% and Disease control rate was 94.6% among patients who had target lesion. Median progression-free survival was 9.4 months (95% CI, 5.4 – 13.4) and median overall survival was 19.6 months (95% CI, 13.9 – 24.3). The most common adverse event of grade 3 or higher was neutropenia (61.7%). Febrile neutropenia was 8.3%. Conclusions: It seemed that nab-P+GEM was effective for patients with LAPC. Prospective and further investigation in more cases is expected. Legal entity responsible for the study: Hokkaido Gastrointestinal Cancer Study Group. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.